Determinants of Savings Behaviour Among University Students in Sabah, Malaysia. - Amer Azlan Abdul Jamal; Wijaya Kamal Ramlan; Rosle Mohidin; Zaiton Osman (2016)
Most economists believe that anincrease in savings will flourish the growth of economic activities and further strengthening the economy of that particular nation. However, recent news report stated that household debts in Malaysia have gradually risen to 86.8% of its GDP, making it the most highly levered households in Asia. As a result, total household savings remained insufficient and they are mostly under prepared for retirement. What is more worrying is the young adults are reported to be the main group trapped into this financial complexity. This issue has raised concern on the needs to educate the young adults the fundamental value of supplementing their savings in order to ensure sufficiency of their future retirement income. With regard to savings behaviour, the needs of savingsamongst individuals differ from one to another as a result of different mind-set, behaviour, knowledge, and social environment. The research therefore intends to (i) investigate factors that influence savings behaviour amongst university and college students; and (ii) to examine the role of financial attitudes in mediating the relationship between financial literacy and savings behaviour. Structured questionnaires were distributed to 1728 undergraduate students studying at higher learning institutions across major cities in Sabah using convenient sampling technique. Structural equation modelling was applied using the SMART-PLS software v.2.0 to execute the analyses. Results revealed that family involvement, peer influence, self -control and financial literacy play an important role in nurturing students’ savings behaviour. In addition, students are said to have more favourable financial attitude when they are financially literate. Financial attitude however, does not have the mediation effect on the relationship between financial literacy and savings behaviour